2020
DOI: 10.1155/2020/3798537
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Single-Level Open and Minimally Invasive Transforaminal Lumbar Interbody Fusions Presenting a Learning Curve

Abstract: Background. Comparison of single-level open and minimally invasive transforaminal lumbar interbody fusions (O-TLIF and MI-TLIF) of a single surgeon and presentation of his MI-TLIF learning curve in a retrospective observational cohort study. Methods. 27 MI-TLIF and 31 O-TLIF patients, performed between 03/01/2013 and 03/31/2018, were compared regarding the operative time, blood loss, blood transfusion frequency, postoperative length of stay (LOS), and adverse events. An overall comparison of pre- and postopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…A consistent theme among the studies was a gradual decrease in operative duration; 7 of the studies reported statistically significant decreases in operative duration from during the learning curve to after completion, 6,8,[15][16][17][18][19] confirming that surgeons become more efficient with experience. Furthermore, when comparing operative durations between studies, monotonic trends revealed a significant negative correlation between operative durations of cases during the learning curve and the year studies were published.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…A consistent theme among the studies was a gradual decrease in operative duration; 7 of the studies reported statistically significant decreases in operative duration from during the learning curve to after completion, 6,8,[15][16][17][18][19] confirming that surgeons become more efficient with experience. Furthermore, when comparing operative durations between studies, monotonic trends revealed a significant negative correlation between operative durations of cases during the learning curve and the year studies were published.…”
Section: Discussionmentioning
confidence: 91%
“…The number of patients in each study varied widely as well. For example, while Lee et al 8 included 90 patients and reported completion of the learning curve at 44 cases, Kovari et al 19 only included 27 patients and reported completion at 14 cases. It is difficult to directly compare these 2 endpoints when the overall cohort size of one study is smaller than the learning curve of the other.…”
Section: Discussionmentioning
confidence: 99%
“…This site's experience has been that the TOPS surgical technique allows implantation of the device without complications and minimal “fiddle factor.” The average operative time of 102 minutes found in this study is lower than reported durations of 1-level spinal fusion procedures of 142 to 200 minutes. 24-26…”
Section: Discussionmentioning
confidence: 99%
“…Most reports on learning curves or variability across practitioners for invasive treatments for neck or low back pain focus on interventions other than NRT, many of which lack high quality evidence supporting their efficacy and effectiveness. Moreover, they are based on small samples (e.g., ≤150 patients or ≤3 practitioners), do not use multi-level analyses to adjust results for patient prognosis as established by previously validated models, or have been conducted either retrospectively or outside routine practice conditions (e.g., based on data gathered in randomized controlled trials) [ 8 , 9 , 10 , 11 , 12 , 13 , 40 , 41 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. Therefore, it is inappropriate to compare such data with results from this study.…”
Section: Discussionmentioning
confidence: 99%